Proceedings of the 23rd Conference on Formal Methods in Computer-Aided Design - FMCAD 2023 - Nadel, Alexander; Rozier, Kristin Yvonne (Conference Series: Formal Methods in Computer-Aided Design, 2023)
The Conference on Formal Methods in Computer-Aided Design (FMCAD) is an annual conference on the theory and applications of formal methods in hardware and system in academia and industry for presenting and discussing groundbreaking methods, technologies, theoretical results, and tools for reasoning formally about computing systems. FMCAD covers formal aspects of computer-aided system testing.